2002
DOI: 10.1104/pp.003756
|View full text |Cite
|
Sign up to set email alerts
|

Starch Synthesis in Arabidopsis. Granule Synthesis, Composition, and Structure

Abstract: The aim of this work was to characterize starch synthesis, composition, and granule structure in Arabidopsis leaves. First, the potential role of starch-degrading enzymes during starch accumulation was investigated. To discover whether simultaneous synthesis and degradation of starch occurred during net accumulation, starch was labeled by supplying 14 CO 2 to intact, photosynthesizing plants. Release of this label from starch was monitored during a chase period in air, using different light intensities to vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
145
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 34 publications
5
145
0
3
Order By: Relevance
“…They suggested that an unknown mechanism increasingly diverted newly assimilated C toward Suc, leading to a reduced flux of C into starch synthesis rather than the onset of degradation after prolonged periods in the light (Li et al, 1992). It is possible that this pulse-chase experiment failed to detect starch degradation because 14 C starch was buried within the starch granule beneath newly synthesized 12 C starch during the chase and thus protected from degradation occurring at the granule surface (Zeeman et al, 2002). However, it is also possible that the cause of the commonly observed cessation of starch accumulation in continuous light differs between species.…”
Section: Table I Incorporation Of 14 C Into Leaf Fractions Followingmentioning
confidence: 84%
See 1 more Smart Citation
“…They suggested that an unknown mechanism increasingly diverted newly assimilated C toward Suc, leading to a reduced flux of C into starch synthesis rather than the onset of degradation after prolonged periods in the light (Li et al, 1992). It is possible that this pulse-chase experiment failed to detect starch degradation because 14 C starch was buried within the starch granule beneath newly synthesized 12 C starch during the chase and thus protected from degradation occurring at the granule surface (Zeeman et al, 2002). However, it is also possible that the cause of the commonly observed cessation of starch accumulation in continuous light differs between species.…”
Section: Table I Incorporation Of 14 C Into Leaf Fractions Followingmentioning
confidence: 84%
“…The simplifying assumption that leaf starch degradation is low or absent during the light period is supported by pulse-chase experiments with 14 CO 2 , which failed to detect significant starch degradation in standard light periods in pea (Pisum sativum; Kruger et al, 1983), pepper (Capsicum annuum; Grange, 1984), wild-type Arabidopsis (Arabidopsis thaliana; Walters et al, 2004;Zeeman et al, 2002), and tobacco (Nicotiana tabacum; Häusler et al, 1998) leaves (limitations of this approach are discussed in Supplemental Text S1). However, starch degradation may occur during long periods in continuous light, in some mutants with chloroplast export deficiencies, and in response to acute abiotic stress.…”
mentioning
confidence: 99%
“…PSH1 appears to be dispensable for starch degradation. Zeeman et al (2002) suggested that PHS1 is important for tolerance against abiotic stress because Atphs1 mutants were susceptible for transient water deficiency. Both PHS isoforms, however, were highly regulated during the diurnal cycle and PHS2 is of special interest because it is cytosolic and might play a role in the conversion from starch via maltose into Glc .…”
Section: Discussionmentioning
confidence: 99%
“…It is synthesized mainly during photosynthesis in the light period buffering CO 2 fixation or in storage organs like tubers, bulbs, or seeds (Dennis and Blakeley, 2000). In recent years, numerous studies have been performed to increase knowledge of starch metabolism, including in the model plant Arabidopsis (Arabidopsis thaliana; Zeeman et al, 2002Zeeman et al, , 2004Siedlecka et al, 2003;Smith et al, 2004;Delvallé et al, 2005;Lloyd et al, 2005;Dumez et al, 2006). In most of these studies, plant leaf material of the wild type and mutant lines was used to investigate starch metabolism under different light regimes or altered sugar concentrations.…”
mentioning
confidence: 99%
“…Amylose comprises predominantly linear chains of a-1,4-linked Glc residues, whereas amylopectin exists as a branched a-1,4:a-1,6 D-glucan polymer. Amylopectin accounts for about 75% of the starch weight in reserve starch (Ball et al, 1998) and typically more than 90% in transitory starch (Zeeman et al, 2002).…”
mentioning
confidence: 99%